2005
DOI: 10.1136/oem.2004.015685
|View full text |Cite
|
Sign up to set email alerts
|

Sensitisation to mites in laboratory animal workers with rhinitis

Abstract: Aims: To determine the frequency of sensitisation to mites among rhinitic laboratory animal workers and to clarify whether sensitisation could be occupational. Methods: Skin prick tests (SPT) were performed in 40 subjects who were working with laboratory animals in Kuopio University research units and who had been referred to Kuopio University Hospital for work related rhinitis. The SPT panel consisted of three storage mites, two house dust mites, 11 other common environmental airborne allergens, latex, and 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
(21 reference statements)
0
6
0
1
Order By: Relevance
“…The symptoms began within 3 years after start of exposure in all but one of the mite-positive workers. Investigators concluded that mite sensitization may account for work-related symptoms in cases where laboratory animal allergy is not diagnosed with skin prick test [14]. Laboratory animal allergen is a well-known cause of ORS, and a dose-response relationship appears to exist between level of exposure and risk of disease.…”
Section: Recent Achievements In Occupational Rhinosinusitis Researchmentioning
confidence: 95%
“…The symptoms began within 3 years after start of exposure in all but one of the mite-positive workers. Investigators concluded that mite sensitization may account for work-related symptoms in cases where laboratory animal allergy is not diagnosed with skin prick test [14]. Laboratory animal allergen is a well-known cause of ORS, and a dose-response relationship appears to exist between level of exposure and risk of disease.…”
Section: Recent Achievements In Occupational Rhinosinusitis Researchmentioning
confidence: 95%
“…In addition to specific animal allergens, there is evidence from chamber studies of individuals with LAA that other allergens such as dust mites may play a role in the development of occupational rhinitis and other allergies in the laboratory animal environment (Ruoppi et al, 2004(Ruoppi et al, , 2005.…”
Section: Allergensmentioning
confidence: 99%
“…The large difference between the prevalence of symptomatic workers and of symptomatic workers with specific sensitization to rat or mouse suggests a role for irritants (Kacergis et al, 1996;Kogevinas et al, 2007) or allergens not looked for in the study, e.g. sensitization to storage or house dust mites (Hollander et al, 1996;Ruoppi et al, 2005), other animal allergens (Botham et al, 1987), powdered latex gloves, drugs, or anesthetics.…”
Section: Introductionmentioning
confidence: 95%